2015
DOI: 10.1177/2167702614560746
|View full text |Cite
|
Sign up to set email alerts
|

Positive Imagery-Based Cognitive Bias Modification as a Web-Based Treatment Tool for Depressed Adults

Abstract: Depression is a global health problem requiring treatment innovation. Targeting neglected cognitive aspects may provide a useful route. We tested a cognitive-training paradigm using positive mental imagery (imagery cognitive bias modification, imagery CBM), developed via experimental psychopathology studies, in a randomized controlled trial. Training was delivered via the Internet to 150 individuals with current major depression. Unexpectedly, there was no significant advantage for imagery CBM compared with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
249
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 197 publications
(270 citation statements)
references
References 90 publications
(171 reference statements)
15
249
3
3
Order By: Relevance
“…The positive imagery CBM intervention as implemented in the trial (Blackwell et al., 2015) comprised an initial face‐to‐face introductory session at the research center followed by 12 sessions completed from home over the Internet. Six sessions used audio presentation of training stimuli, in which participants listened to brief descriptions of everyday situations that were structured so that they started ambiguous as to their potential resolution but always ended positively (for example, “As you are getting dressed in the morning, you think about the day ahead.…”
Section: Case Illustrationmentioning
confidence: 99%
See 4 more Smart Citations
“…The positive imagery CBM intervention as implemented in the trial (Blackwell et al., 2015) comprised an initial face‐to‐face introductory session at the research center followed by 12 sessions completed from home over the Internet. Six sessions used audio presentation of training stimuli, in which participants listened to brief descriptions of everyday situations that were structured so that they started ambiguous as to their potential resolution but always ended positively (for example, “As you are getting dressed in the morning, you think about the day ahead.…”
Section: Case Illustrationmentioning
confidence: 99%
“…(2015), and the reduction to zero of Theresa's anhedonic symptoms. Further, the hypothesised link between the positive imagery and behavioral activation fits with the observation that participants in the positive imagery condition in the trial showed initially greater increases in self‐reported behavioral activation (as measured by the BADS) than those in the control condition (Renner, Ji, Pictet, Holmes, & Blackwell, 2016).…”
Section: Clinical Practices and Summarymentioning
confidence: 99%
See 3 more Smart Citations